Analysis of sagittal profile of spine using 3D ultrasound imaging: a phantom study and preliminary subject test - Lee, Timothy Tin-Yan; Cheung, James Chung-Wai; Law, Siu-Yu; To, Michael Kai Tsun; Cheung, Jason Pui Yin; Zheng, Yong-Ping (Computer methods in biomechanics and biomedical engineering., 2020)
Radiographic Cobb's angle is the gold standard for evaluation of spinal curvature, however, X-ray is ionising. In contrast, ultrasound is non-ionising and inexpensive. However, no study has reported the reliability and accuracy of ultrasound on sagittal curvature analysis. Ultrasound and X-ray scanning were conducted on 16 sets of spine phantoms with different deformities. Intra-rater and inter-rater reliability, correlations, mean absolute differences (MAD) and linear regression of ultrasound spinous process angles (USSPA), X-ray spinous process angles (XSPA) and X-ray Cobb's angles (XCA) together with the intra-operator reliability of USSPA were investigated. In addition, USSPA and XCA of five AIS subjects were obtained using the ultrasound system. In the phantom study, excellent intra-rater and inter-rater reproducibility for the three angles and excellent intra-operator reproducibility for USSPA were demonstrated. Good to moderate or better correlations were obtained among the angles. All three angles indicated positive linear relationships with MAD ≤ 6.0°. The results of the preliminary study demonstrated a high intra-reliability for the ultrasound measurements. The measured difference between the USSPA and XCA methods was 6.3° ± 5.4°. The results showed that ultrasound is feasible for measuring sagittal curvature and has the potential for monitoring the curve progression and evaluating sagittal spinal profiles.